Synthesis and characterization of zinc oxide/reduced graphene oxide hybrid photocatalysts for degradation of methyl orange - Yuen, Marilyn Sok Wen (2017)
The recalcitrant nature and toxicity of organic pollutants in wastewater to mankind have led to extensive research on the usage of semiconductor based heterogeneous photocatalysis, in particular zinc oxide (ZnO). In this study, zinc oxide/reduced graphene oxide (ZnO/rGO) hybrid photocatalysts with varying graphene oxide (GO) to zinc salt volume ratio (0:100, 5:100, 10:100 and 20:100) were synthesized by precipitation method using zinc acetate dihydrate, ammonium hydroxide and graphene oxide (1 mg/mL) as precursors followed by thermal reduction. The product was denominated as ZnO, ZnO/rGO5, ZnO/rGO10 and ZnO/rGO20. The samples were characterized using X-ray powder diffraction (XRD), transmission electron microscopy (TEM), field emission scanning electron microscopy (FESEM), raman spectroscopy and particle size analysis (PSA). Surface area and porosity analysis and the band gap energy of the photocatalysts were determined by the Brunauer- Emmett-Teller method (BET) and UV-visible spectroscopic analysis. The introduction of graphene into ZnO was found to alter the physicochemical properties of the ZnO particles by lowering its band gap energy, reducing both particle and pore sizes and increasing its specific surface area and pore volume. The corresponding photocatalytic performance of the samples was then investigated by degrading methyl orange (MO) under UV light. The hybrid photocatalysts with ZnO particles decorated on the graphene sheet were found to achieve significant increased photocatalytic activity compared to ZnO with ZnO/rGO10 hybrid photocatalyst achieved fourfold enhancement in rate constant that of ZnO and about 40 % enhancement in the photocatalytic activity for the removal of 10 ppm MO within 3 hours. This was attributed to the presence of graphene that promotes efficient photoinduced charge separation by inhibiting the recombination of electron-hole pairs and enhanced dye adsorptivity on the catalyst’s surface via π-π interaction between MO and graphene sheet with delocalised conjugated π structure. Changes in textural properties and band gap energy of ZnO particles in the hybrid increased the light absorption and stronger adsorption of MO on the surface of the catalyst, thereby increasing its photocatalytic effciency. Increasing the GO content (ZnO/rGO20) however led to a decrement in photocatalytic activity by shielding the active sites on the surface of the catalyst, reducing light absorption. The MO degradation was at its optimum with 96.78% of 10 ppm MO removed within 3 hours using 0.5 g of ZnO/rGO10 hybrid photocatalyst, obeying the pseudo-first-order kinetics according to the Langmuir-Hinshelwood model. The reusability of the ZnO/rGO10 hybrid photocatalyst was confirmed by retaining 83% of activity after four consecutive cycles.